Pengaruh Gaya Kepemimpinan dan Kompensasi terhadap Kepuasan Kerja Karyawan di PT Putra Agro Nenggala - Israwati Israwati; Rahmat Sale Manalu (Jurnal Mahasiswa Manajemen dan Akuntansi, 2025)
This study aims to determine the effect of leadership style and satisfaction on employee job satisfaction Agree partially and simultaneously at PT Putra Agro Nenggala. This study is a causal associative study with a quantitative approach. The variables of this study are leadership style, satisfaction and employee job satisfaction. The population in this study were all employees of PT Putra Agro Nenggala totaling 76 people and 76 employees were taken as research samples using saturated sampling techniques. The data collection technique used a questionnaire and the data analysis used was multiple linear regression. The results of this study indicate that (1) Leadership Style partially does not affect Employee Job Satisfaction, it can be seen from the results of SPSS processing obtained a sig value of 0.089> 0.05 and a t count value of 1.723 <t table 1.992 then H1 is accepted. (2) Compensation affects Employee Job Satisfaction can be seen from the sig value of 0.000 <0.05 and a t count value of 5.023> t table 1.992 then H2 is accepted. (3) Simultaneously, both independent variables, namely Leadership Style and Compensation, have an effect on Employee Job Satisfaction, as can be seen from the value of 0.000 < 0.05. The effective contribution of both independent variables, namely Leadership Style and Compensation, can be seen from the R2 results obtained at 43.3%, while the remaining 56.7% is influenced by other variables. Meanwhile, the variable with the most dominant contribution is the Compensation variable with a t count of 5.023.